A unique case of extrapulmonary sarcoidosis on F18 FDG PET/CT: “Tiger man” - Uslu Biner, Inci; Aslan, Seval; Ak Sivrikoz, Ilknur; Seker, Nazli Sena (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Sarcoidosis is a systemic granulomatous disease in which muscle involvement is a rare extrapulmonary manifestation. We present the case of a 34-year-old man with shortness of breath lasting for three months.  Computerized tomography showed intrathoracic lymph nodes and perihilar consolidations in both lungs. She received treatment for pneumonia, but because of insufficient regression, she was referred to our hospital's chest diseases department for further examination. Laboratory results showed an elevated calcium. We conducted an F-18 FDG PET CT scan because the clinicians suspected cancer. PET/CT scan demonstrated hypermetabolism in bilateral lung parenchyma, multiple lymph nodes, the spleen, muscles, and cutaneous/subcutaneous lesions. With the guidance of PET/CT with a suspicion of lymphoproliferative diseases, an axillary lymph node biopsy revealed granulomas; sarcoidosis was assumed, and corticosteroids were started. This case shows rarely seen muscle involvement of sarcoidosis by emphasizing the ability of  PET/CT in detecting extrapulmonary involvement of the disease